Centre-staging beneficiaries in charity accountability: Insights from an Islamic post-secular perspective. (March 2021) - Yasmin, Sofia; Ghafran, Chaudhry; Haslam, Jim
Highlights: Reconceptualise meaning of charity towards achieving social justice. Devolved approach with emphasis on trust, reciprocity and dialogic accountability. Shifting focus away from rights of funders and donors to rights of beneficiaries. A greater role for beneficiaries in day to day NGO life. Abstract: In recent times there has been increased concern to give emphasis to beneficiaries in the context of charity accountability. We here explore insights from a post-secular perspective for making beneficiaries centre-stage in charity accountability – in part inspired by calls, in the work of McPhail and others, to open up to a post-secular perspective on accounting and related practices. Our contention is that theoretically and contextually appreciating tenets and practices of religion vis-à-vis centre-staging charity beneficiaries indicates potentially positive insights for charity accountability more generally: towards the better realisation of deeper and more holistic emancipatory practice. In this regard, we here focus upon a contextual appreciation of tenets and practices of Islamic charity.